Communicating at work : - Adler, Ronald B. (McGraw-Hill Co., 1996)
Highly regarded for its clarity, wealth of examples and practical suggestions, this successful text offers a comprehensive look at oral communication in business and professional setting, from preparing and delivering presentations to interviewing, from group problem solving to interpersonal communication in the workplace. The addition of a co-author, Jeannie Elmhorst, has given the book a streamlined organization and a fresh pedagogical approach.